Multiple Meanings of "Gift" and its Value for Organ Donation. (May 2015) - Shaw, Rhonda M.; Webb, Robert
The "gift of life" metaphor is used to promote organ donation where commercialization is prohibited. In this article, we explore how multiple parties involved in organ transfer procedures think of gift terminology by drawing on interview data with transplantation specialists, organ transplant recipients, living directed donors and living nondirected donors. The interviews took place across New Zealand between October 2008 and May 2012, in participants' homes and hospital workplaces. The interviews were transcribed verbatim, coded manually, and thematically analyzed. Although gift language is often viewed as clear-cut, the gift trope has multiple meanings for different constituent and cultural groups, ranging from positive descriptors to obscuring and romanticizing the complexities of transplantation processes. To account for these multiple perspectives, we suggest new ethical models to capture the nuanced phenomenon of organ transfer in ways that recognize the full range of donation and reception experiences.